Understanding the endoplasmic reticulum – mitochondrial crosstalk in the alveolar epithelium in lung fibrosis - Bickelhaupt, Jessica; Justus Liebig University Giessen (My University, 2023)
About 20% of mitochondria in a cell are juxtaposed to the ER forming mitochondria associated membranes (MAMs). These dynamic, physical, proteinaceous contacts between ER-mitochondria are required for several physiological functions including Ca2+ transfer and signaling molecules that are important to govern critical cell fate decisions. However, under conditions of ER stress, mitochondria relocate to the perinuclear region to tighten their contact with the ER and display an increase in Ca2+ uptake, ATP production and oxygen consumption. Upon persistent ER stress, when the unfolded protein response (UPR) fails to resolve such stress, pro-apoptotic signals are triggered leading to apoptotic cell death and these mechanisms have been linked to alterations in the MAMs and MAM proteins. Characteristic MAM proteins involved are inositol 1,4,5-triphosphate receptors (IP3R), sigma 1 receptor (SigmaR1), calnexin. Certain core mitochondrial proteins, namely dynamin-related protein 1 (DRP1) and mitochondrial fission and fusion regulating proteins, Mitofusin 1 and 2 (MNF1/MFN2) respectively, are also involved in modulating interaction between these two organelles. Another multifaceted sorting protein, phosphofurin acidic cluster sorting protein-2 (PACS2), is also located at the ER-mitochondria interface. An absence of PACS2 leads to mitochondrial fragmentation and uncoupling from the ER. Persistent ER stress and mitochondrial dysfunction are well-documented pathological mechanisms in the lung alveolar epithelial cells type II (AECII) of patients with idiopathic pulmonary fibrosis (IPF). Although multiple cell types are indicated to contribute to the pathogenesis, chronic injury to the AECII is an accepted key event that triggers the disease process in IPF. In this regard, extensive ER stress signature molecules in the AECII of sporadic IPF patients is reported and that induction of the terminal ER stress pro-apoptotic transcription factor CHOP is sufficient enough to drive lung epithelial cell apoptosis and pro-fibrotic signaling. Supporting this, in familial cases with mutations in the surfactant protein C (SP-C) gene which leads to its protein misfolding, a ‘maladaptive’ pro-apoptotic ER stress has been reported. In this study, the contribution of MAM proteins towards apoptosis in response to ER stress have been analyzed. The induction of CHOP or pathological ER stress resulted in a decrease in ER-mitochondrial contacts in addition to a decrease in PACS2 as well as a dysregulation of its interactor, TRPV1 which in turn drove cells to apoptosis. A similar reduction in PACS2 as well as altered TRPV1 proteins were observed in cells stably overexpressing pathologic mutation SP-CΔexon4 and in AECII of IPF patients. Finally, treatment of ex-vivo, three-dimensional lung slices or precision cut lung slices (PCLS) of IPF patients with the TRPV1 modulating drug CPS decreased apoptosis and restored both TRPV1 and PACS2 protein levels. In conclusion, this study shows that targeting of the PACS2-TRPV1 axis represents an interesting novel, epithelial-protective approach in IPF.
Keywords: ddc:610